Oral delivery of oligomeric procyanidins in Apple Poly® enhances type I IFN responses in vivo. Issue 5 (13th January 2014) - Snyder, Deann T; Robison, Amanda; Kemoli, Sharon; Kimmel, Emily; Holderness, Jeff; Jutila, Mark A; Hedges, Jodi F
Abstract : Augmentation of responses to type I IFN following ingestion of Apple Poly® may have broad therapeutic application to enhance antiviral immunity, or suppress inflammation. ABSTRACT: Type I IFN signaling is a central pathway that provides critical innate protection from viral and bacterial infection and can have regulatory outcomes in inflammatory settings. We determined previously that OPCs contained in the dietary supplement APP enhanced responses to type I IFN in vitro. Here, we confirm that OPCs from two different sources significantly increased pSTAT1, whereas a monomeric form of procyanidin did not. We hypothesized that similar responses could be induced in vivo following ingestion of APP. Ingestion of APP before injection of polyI:C enhanced in vivo responses to type I IFNs in mice. When human subjects ingested APP, enhanced responses to type I IFN and enhanced pSTAT1 ex vivo were detected, whereas ingestion of RES, a monomeric polyphenol, induced minimal such changes. Polyphenols are best known for induction of anti-inflammatory and antioxidant responses; however, our findings suggest a unique, nonantioxidant aspect of OPCs that is broadly applicable to many disease settings. The capacity of oral OPCs to enhance type I IFN signaling in vivo can augment innate protection and may, in part, contribute to the noted anti-inflammatory outcome of ingestion of OPCs from many sources.